2017
DOI: 10.29063/ajrh2017/v21i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Causes of Change in Adolescent Girls’ Sexual Behaviour in Begoro, Ghana

Abstract: There is a changing trend in adolescent girls' sexual and reproductive behaviour in Ghana. However, contemporary perspectives on adolescent girls' sexual behaviours are largely missing hence this study. Thematic analysis of data collected through in-depth interviews with adolescent girls and community members as well as focus group discussions with adolescent boys identified several factors accounting for the changes in adolescent girls' sexual and reproductive behaviour. These factors include changes in girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The long wait between puberty and marriage has contributed to the increasing number of adolescents having sex and bearing children out of wedlock (Agunbiade, 2014; Gyan, 2017; Moloney, Hunt, Joe-Laidler, & MacKenzie, 2011; Zwang & Garenne, 2008). Adolescents are postponing age at marriage because of factors such as urbanization, migration, and formal education (Addai, 2000; Awusabo-Asare, Abane, & Kumi-Kyereme, 2004; Biddlecom, Gregory, Lloyd, & Mensch, 2008; Glover et al, 2003; Gyan, 2017). Increasingly, more adolescents are postponing the age at marriage; however, the age at first sex remains low.…”
Section: Introductionmentioning
confidence: 99%
“…The long wait between puberty and marriage has contributed to the increasing number of adolescents having sex and bearing children out of wedlock (Agunbiade, 2014; Gyan, 2017; Moloney, Hunt, Joe-Laidler, & MacKenzie, 2011; Zwang & Garenne, 2008). Adolescents are postponing age at marriage because of factors such as urbanization, migration, and formal education (Addai, 2000; Awusabo-Asare, Abane, & Kumi-Kyereme, 2004; Biddlecom, Gregory, Lloyd, & Mensch, 2008; Glover et al, 2003; Gyan, 2017). Increasingly, more adolescents are postponing the age at marriage; however, the age at first sex remains low.…”
Section: Introductionmentioning
confidence: 99%
“…A study on culture and sexual behaviors among Iranian and New Zealand women found that sexual behaviors and sexual desire and pleasure were related to community culture, beliefs and past experiences regarding sexual activities [44]. A change in the social context or diversity of socialization led to a change in risky behaviors and sexual behaviors among youths in Ghana [45]. Moreover, a study by Mpondo et al [46] reported that apart from culture, parenting styles and school curriculum affected risk behaviors, including sexual behaviors, of youths.…”
Section: Discussionmentioning
confidence: 99%